Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Niche breadth of Amazonian trees increases with niche optimum across broad edaphic gradients - Jason Vleminckx; Oscar Valverde Barrantes; Claire Fortunel; C. E. Timothy Paine; David Bauman; Julien Engel; Pascal Petronelli; Nállarett Dávila; Marcos Rios; Elvis Harry Valderrama Sandoval; Italo Mesones; Elodie Allié; et al. (Ecology, 2023)
Understanding how biotic interactions and environmental filtering mediated by soil properties shape plant community assembly is a major challenge in ecology, especially when studying complex and hyperdiverse ecosystems like tropical forests. To shed light on the influence of both factors, we examined how the edaphic optimum of species (their niche position) related to their edaphic range (their niche breadth) along different environmental gradients and how this translates into functional strategies. Here we tested four scenarios describing the shape of the niche breadth—niche position relationship, including one neutral scenario and three scenarios proposing different relative influences of abiotic and biotic factors on community assembly along a soil resource gradient. To do so, we used soil concentration data for five key nutrients (N, P, Ca, Mg, and K), along with accurate measurements of 14 leaf, stem, and root traits for 246 tree species inventoried in 101 plots located across Eastern (French Guiana) and Western (Peru) Amazonia. We found that species niche breadth increased linearly with species niche position along each soil nutrient gradient. This increase was associated with more resource acquisitive traits in the leaves and the roots for soil N, Ca, Mg, and K concentration, while it was negatively associated with wood density for soil P concentration. These observations agreed with one of our hypothetical scenarios in which species with resource conservation traits are confined to the most nutrient‐depleted soils (abiotic filter), but they are outperformed by faster‐growing species in more fertile conditions (biotic filter). Our results refine and strengthen support for niche theories of species assembly while providing an integrated approach to improving forest management policies.

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Defaunation changes leaf trait composition of recruit communities in tropical forests in French Guiana - Rens W. Vaessen; Patrick A. Jansen; Cécile Richard‐Hansen; René G. A. Boot; Thomas Denis; Géraldine Derroire; Pascal Petronelli; Jesse S. de Vries; Kathryn E. Barry; Hans ter Steege; Marijke van Kuijk (Ecology, 2023)
Hunting impacts tropical vertebrate populations, causing declines of species that function as seed dispersers and predators, or that browse seedlings and saplings. Whether and how the resulting reductions in seed dispersal, seed predation, and browsing translate to changes in the tree composition is poorly understood. Here, we assess the effect of defaunation on the functional composition of communities of tree recruits in tropical rainforests in French Guiana. We selected eight sites along a gradient of defaunation, caused by differences in hunting pressure, in otherwise intact old‐growth forests in French Guiana. We measured shifts in functional composition by comparing leaf and fruit traits and wood density between tree recruits (up to 5 cm diameter at breast height) and adults, and tested whether and how these compositional shifts related to defaunation. We found a positive relationship with defaunation for shifts in specific leaf area, a negative relationship for shifts of leaf toughness and wood density, and a weak relationship for shifts in fruit traits. Our results suggest that the loss of vertebrates affects ecological processes such as seed dispersal and browsing, of which browsing remains understudied. Even though these changes sometimes seem minor, together they result in major shifts in forest composition. These changes have long‐term ramifications that may alter forest dynamics for generations.

Long‐term influence of early human occupations on current forests of the Guiana Shield - Guillaume Odonne; Martijn van den Bel; Maxime Burst; Olivier Brunaux; Miléna Bruno; Etienne Dambrine; Damien Davy; Mathilde Desprez; Julien Engel; Bruno Ferry; Vincent Freycon; Pierre Grenand; et al. (Ecology, 2019)
To decipher the long‐term influences of pre‐Columbian land occupations on contemporary forest structure, diversity, and functioning in Amazonia, most of the previous research focused on the alluvial plains of the major rivers of the Amazon basin. Terra firme, that is, nonflooded forests, particularly from the Guiana Shield, are yet to be explored. In this study, we aim to give new insights into the subtle traces of pre‐Columbian influences on present‐day forests given the archaeological context of terra firme forests of the Guiana Shield. Following archaeological prospects on 13 sites in French Guiana, we carried out forest inventories inside and outside archaeological sites and assessed the potential pre‐Columbian use of the sampled tree species using an original ethnobotanical database of the Guiana Shield region. Aboveground biomass (320 and 380 T/ha, respectively), basal area (25–30 and 30–35 m 2 /ha, respectively), and tree density (550 and 700 stem/ha, respectively) were all significantly lower on anthropized plots (As) than on nonanthropized plots ( NA s). Ancient human presence shaped the species composition of the sampled forests with Arecaceae, Burseraceae, and Lauraceae significantly more frequent in As and Annonaceae and Lecythidaceae more frequent in NA s. Although alpha diversity was not different between As and NA s, the presence of pre‐Columbian sites enhances significantly the forest beta diversity at the landscape level. Finally, trees with edible fruits are positively associated with pre‐Columbian sites, whereas trees used for construction or for their bark are negatively associated with pre‐Columbian sites. Half a millennium after their abandonment, former occupied places from the inner Guiana Shield still bear noticeable differences with nonanthropized places. Considering the lack of data concerning archaeology of terra firme Amazonian forests, our results suggest that pre‐Columbian influences on the structure (lower current biomass), diversity (higher beta diversity), and composition (linked to the past human tree uses) of current Amazonian forests might be more important than previously thought.

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.